Expression of microRNA-331 can be used as a predictor for response to therapy and survival in acute myeloid leukemia patients. (May 2015) - Butrym, Aleksandra; Rybka, Justyna; Baczyńska, Dagmara; Tukiendorf, Andrzej; Kuliczkowski, Kazimierz; Mazur, Grzegorz
Aim: Aberrant expression of microRNAs (miRs) has been proved to have a role in acute myeloid leukemias (AML), but there is no information on miR-331 in AML.Materials & methods: miR-331 expression has been analyzed using reverse-transcription polymerase chain reaction (RT-PCR) in 95 bone marrow specimens from newly diagnosed AML patients in comparison with 20 healthy subjects.Results: miR-331 was upregulated in AML patients and its expression seemed to influence remission achieving and death risk. The time of remission duration in patients with complete remission was longer in subjects with miR-331 downregulation after induction chemotherapy.Conclusion: we showed for the first time that miR-331 higher expression appears to be correlated with worse response to therapy and shorter survival of AML patients.